Combining CHA2DS2-VASc score into RCRI for prediction perioperative cardiovascular outcomes in patients undergoing non-cardiac surgery: a retrospective pilot study - Song-Yun Chu (BMC, 2021)
Abstract Background Treatment decisions in patients undergoing non-cardiac surgery are based on clinical assessment. The Revised Cardiac Risk Index (RCRI) is pragmatic and widely used but has only moderate discrimination. We aimed to test the efficacy of the CHA2DS2-VASc score and the combination of CHA2DS2-VASc and RCRI to predict perioperative risks for non-cardiac surgery. Methods This pre-specified analysis was performed in a retrospective cohort undergoing intra-abdominal surgery in our center from July 1st, 2007 to June 30th, 2008. The possible association between the baseline characteristics (as defined by CHA2DS2-VASc and RCRI) and the primary outcome of composite perioperative cardiac complications (myocardial infarction, cardiac ischemia, heart failure, arrhythmia, stroke, and/or death) and secondary outcomes of individual endpoints were explored using multivariate Logistic regression. The area under the receiver operating characteristic curve (C-statistic) was used for RCRI, CHA2DS2-VASc, and the combined models, and the net reclassification improvement (NRI) was calculated to assess the additional discriminative ability. Results Of the 1079 patients (age 57.5 ± 17.0 years), 460 (42.6%) were women. A total of 83 patients (7.7%) reached the primary endpoint. Secondary outcomes included 52 cardiac ischemic events, 40 myocardial infarction, 20 atrial fibrillation, 18 heart failure, four strokes, and 30 deaths. The endpoint events increased with the RCRI and CHA2DS2-VASc grade elevated (P < 0.05 for trend). The RCRI showed a moderate predictive ability with a C-statistics of 0.668 (95%CI 0.610–0.725) for the composite cardiac outcome. The C-statistics for the CHA2DS2-VASc was 0.765 (95% CI 0.709–0.820), indicating better performance than the RCRI (p = 0.011). Adding the CHA2DS2-VASc to the RCRI further increased the C-statistic to 0.774(95%CI 0.719–0.829), improved sensitivity, negative predictive value, and enhanced reclassification in reference to RCRI. Similar performance of the combined scores was demonstrated in the analysis of individual secondary endpoints. The best cut-off of a total of 4 scores was suggested for the combined CHA2DS2-VASc and RCRI in the prediction of the perioperative cardiac outcomes. Conclusions The CHA2DS2-VASc score significantly enhanced risk assessment for the composite perioperative cardiovascular outcome in comparison to traditional RCRI risk stratification. Incorporation of CHA2DS2-VASc scores into clinical-decision making to improve perioperative management in patients undergoing non-cardiac surgery warrants consideration.